Withdrawal to the exemption of the Tax on General Sales (IGV) and the financial growth of the companies of the dairy sector of Cañete – 2015 - Malaspina Chuque, Javier Jesús Jesús (2018)
Objective: The study aims to demonstrate the existence of a relationship between the waiver of IGV exemption and the financial growth of companies in the Milk Sector of Cañete (Lima, Peru) in 2015. Methods: To develop the research, the quantitative approach has been used, the type and design of the research is applied and not experimental. It is of a cross-sectional nature, which was applied to the managers of the livestock companies of the milk Sector that desisted to the exemption of the IGV from 2010 to 2014, with a sample of 25 UAA (Animated Analysis Units) subject to study. Results: The techniques used were surveys and the technique of bibliography cards. Once obtained the results, they were tabulated. It is necessary to indicate that the data has been processed with the statistical software of Microsoft Excel. Conclusions: From the processing of collected data and the analysis of the results, it was verified that the withdrawal to the exemption of the IGV is moderately related to the financial growth of livestock companies in the milk sector of Cañete (Lima, Peru) in the year 2015, when quantitative financial growth was observed in the liquidity and profitability indicators, while the indicators of indebtedness and economic management remained without any particular effect.